ANALYSIS OF FACTORS AFFECTING THE QUALITY OF GOVERNMENT FINANCIAL STATEMENTS OF BINJAI CITY WITH WORK MOTIVATION AS MODERATING VARIABLES - Fitri, Yulia (Asosiasi Dosen Akuntansi Indonesia, 2018)
This study objective of the research was to analysethe influence of quality of human resources, the implementation of regional financial information systems, internal control system and the implementation of government accounting standards on the quality of financial statements in the Binjai City Government with work motivation as a moderating variable. The research used comparative causal method. The population and sample in this research are Head of Unit work of Local Government (SKPD), Finance Administration Official of SKPD and SKPD Expenditure Treasurer amounting to 99 (ninety nine) persons in 33 (thirty three) SKPD as Binjai City. The data were processed by using Smart Partial Least Square (PLS) program. The results of this study indicate that the quality of human resources, the implementation of regional financial information systems, internal control system, the implementation of government accounting standards and work motivation significantly influence the quality of financial statements, while the implementation of government accounting standards have no significant effect on the quality of financial statements.